A taxonomic resolution assessment for deep-pelagic fish assemblage analysis in a high-diversity ecosystem - Krista N. Scheuerman; Tamara M. Frank; Tracey T. Sutton; Rosanna J. Milligan (Frontiers in Marine Science, 2026)
The species number of mesopelagic (200–1000 m depth) fishes is extremely rich in the Gulf of Mexico. The aim of this study is to evaluate whether coarser taxonomic resolutions (genus, family, order) can provide informative and reliable measures of fish assemblage structure when species-level identification is not available, and to assess how taxonomic resolution and data transformation influence the ability to discriminate among assemblages across well-established ecological gradients of depth and diel cycle in an oceanic ecosystem. A better understanding of these effects can inform analytical decisions about taxonomic sufficiency when using data that are not, or cannot be, resolved to species level, a common occurrence in deep-sea systems whose faunal inventories are incomplete. This study analyzed assemblage structure patterns in deep-pelagic fishes collected with a large-mesh, commercial-sized, high-speed rope trawl in the Gulf of Mexico from the epipelagic, mesopelagic, and upper bathypelagic zones (0– 1800 m, collectively). Assemblage compositions were compared at four taxonomic levels (species, genus, family, order) and six data transformations between sampling events collected during the day and at night, and across two depth strata. Assemblage structures were analyzed using taxonomic ratios, ANOSIM analyses, and a 2 nd Stage resemblance coefficient analysis. The results show that genus-resolution data provided similar assemblage discrimination (94% effectiveness) as species data, with family and order data providing less suitable substitutions (65% and 8% respectively). Family- and order-level analyses were unable to discriminate between daytime and nighttime assemblages based on depth as effectively as species- and genus-level data. Second-stage analyses indicated that dissimilarities between taxonomic levels were dependent on the transformation applied, with the strongest data transformations leading to greater dissimilarity between taxonomic levels. Overall, these results suggest that in many cases where species-resolution data are not available, genus-level data can be used as a meaningful proxy to characterize deep-pelagic fish assemblages with respect to major ecological drivers, with the proviso that strong data transformations can amplify taxonomic differences.

Past trajectory of a Northwest Europe socio-ecosystem at the land-sea interface: Case study of the northern watersheds of the Bay of Brest over the last 150 years - C. Valero; A. Penaud; M. Vidal; E. Goubert; P.A. Dessandier; S. Schmidt; E. Glémarec; P. Brigode; L. Bosseboeuf; Y.M. Paulet; J. Sutton; P. Ailliot; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Consistent effects of the Loop Current and associated mesoscale eddies on the vertical distributions of deep-pelagic fishes in a subtropical ocean basin - Rosanna J. Milligan; Tracey T. Sutton (Progress in Oceanography, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Grief Among Oncology Providers: Prevalence and Association with Burnout - Shannon R. McGue; Cameron J. Oswalt; Benjamin T. Berger; Sarah S. Morgan; Sara A. Barlow; Carl F. Pieper; Linda M. Sutton; Matthew K. Labriola; Anthony N. Galanos (Journal of Cancer Education, 2025)

Using pre-release efficacy as a candidate agent prioritisation tool for the weed Trichocereus spachianus (Caryophyllales: Cactaceae) - T. C. Griffith; M. B. Aguirre; G. F. Sutton; L. Chari; I. D. Paterson (BioControl, 2025)
Pre-release efficacy assessments (PREA) can be used to prioritise the most damaging candidate agents for further studies in biological control programmes against invasive alien plants. This study assessed the efficacy of various potential enemies of Trichocereus spachianus (Riccob.) (Caryophyllales: Cactaceae), an invasive cactus in South Africa, in order to prioritise the most damaging candidates for further studies, including host specificity testing. T. spachianus is considered indigenous in Argentina and Bolivia, but the original description was based on a cultivated plant, and it is either very rare or absent in its indigenous range, with no verified records of natural populations. This necessitates the use of new associations collected off close relatives of the target plant as potential biocontrol agents. We evaluated eight potential biocontrol agents by deriving host suitability indices (HSI) and performing efficacy trials. The HSI analysis demonstrated that only one out of the eight candidate agents, a cochineal insect Dactylopius confertus De Lotto (Hemiptera: Dactylopiidae), had high fitness (high survival, fecundity and complete development) on T. spachianus . This helped us eliminate ineffective agents early on in the programme. The cochineal insect was prioritised for efficacy trials, which demonstrated its high potential efficacy, killing approximately 89% of T. spachianus plants over 60 weeks. Taken together, our results indicated that D. confertus is a highly promising potential agent for the biocontrol of T. spachianus in South Africa. By prioritising candidate biocontrol agents based on efficacy prior to host specificity testing, we ensured that the highest priority candidate agent was identified for detailed and resource-intensive host specificity testing.

Crustacean assemblage structure over the Charlie-Gibbs Fracture Zone of the Mid-Atlantic Ridge collected during the 2009 Henry B. Bigelow expedition - Kathryn E. Medina; Rosanna J. Milligan; Tracey T. Sutton; Tamara Frank (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Sensory Evaluation of a Powdered Seaweed Seasoning Blend - T. Sutton; H. Park; K. Crowe-White; A. Ferdous; K. Won; A. Robins; A. Ellis (Journal of the Academy of Nutrition and Dietetics, 2025)

Separation of virus-like particles and nano-emulsions for vaccine development by Capillary Zone Electrophoresis - Yousef S. Elshamy; Caleb Kinsey; Richard R. Rustandi; Adam T. Sutton (Analytica Chimica Acta, 2025)

Uncrewed surface vehicles in the Global Ocean Observing System: a new frontier for observing and monitoring at the air-sea interface - Ruth G. Patterson; Meghan F. Cronin; Sebastiaan Swart; Joana Beja; Johan M. Edholm; Jason McKenna; Jaime B. Palter; Alex Parker; Charles I. Addey; Wieter Boone; Paban Bhuyan; Justin J. H. Buck; et al. (Frontiers in Marine Science, 2025)
Observing air-sea interactions on a global scale is essential for improving Earth system forecasts. Yet these exchanges are challenging to quantify for a range of reasons, including extreme conditions, vast and remote under-sampled locations, requirements for a multitude of co-located variables, and the high variability of fluxes in space and time. Uncrewed Surface Vehicles (USVs) present a novel solution for measuring these crucial air-sea interactions at a global scale. Powered by renewable energy (e.g., wind and waves for propulsion, solar power for electronics), USVs have provided navigable and persistent observing capabilities over the past decade and a half. In our review of 200 USV datasets and 96 studies, we found USVs have observed a total of 33 variables spanning physical, biogeochemical, biological and ecological processes at the air-sea transition zone. We present a map showing the global proliferation of USV adoption for scientific ocean observing. This review, carried out under the auspices of the ‘Observing Air-Sea Interactions Strategy’ (OASIS), makes the case for a permanent USV network to complement the mature and emerging networks within the Global Ocean Observing System (GOOS). The Observations Coordination Group (OCG) overseeing GOOS has identified ten attributes of an in-situ global network. Here, we discuss and evaluate the maturation of the USV network towards meeting these attributes. Our article forms the basis of a roadmap to formalise and guide the global USV community towards a novel and integrated ocean observing frontier.

Mesopelagic Fish Traits: Functions and Trade‐Offs - Henrike Andresen; Leandro Nolé Eduardo; M. Pilar Olivar; P. Daniël van Denderen; Jérôme Spitz; Aurore A. Maureaud; Anik Brind'Amour; Noelle M. Bowlin; Eva García‐Seoane; Tom J. Langbehn; Tracey T. Sutton; Heino O. Fock; et al. (Fish and Fisheries, 2025)
Fishes inhabiting the mesopelagic zone of the world's oceans are estimated to account for the majority of the world's fish biomass. They have recently attracted new attention because they are part of the biological carbon pump and have been reconsidered as a contribution to food security. Hence, there is an urgent need to understand how environmental conditions and species interactions shape their assemblages, and how they contribute to the functioning of marine ecosystems. Trait‐based approaches are valuable for addressing these types of questions. However, the biology and ecology of mesopelagic fishes are understudied compared to fishes in shallow and epipelagic waters. Here, we synthesise existing knowledge of traits of mesopelagic fishes and relate them to their role in survival, feeding and growth and reproduction, the key functions that contribute to fitness. Vertical migrations, specialised vision and the use of bioluminescence are among the most striking adaptations to the conditions in the mesopelagic realm. Many traits are interrelated as a result of trade‐offs, which may help to understand selection pressures. While morphological traits are straightforward to observe, major knowledge gaps exist for traits that require frequent sampling, assessment under experimental conditions or age determination. The unique adaptations of mesopelagic fishes need to be included in management strategies as well as fundamental research of the habitat.

Climate Extremes in the New Zealand Region: Mechanisms, Impacts and Attribution - M. James Salinger; Kevin E. Trenberth; Howard J. Diamond; Erik Behrens; B. Blair Fitzharris; Nicholas Herold; Robert O. Smith; Phil J. Sutton; Michael C. T. Trought (International Journal of Climatology, 2024)
As global surface temperatures have increased with human‐induced climate change, notable compound climate extremes in the New Zealand (NZ) region associated with atmospheric heatwaves (AHWs) and marine heatwaves (MHWs) have occurred in the past 6 years. Natural modes of variability that also played a key role regionally include the Interdecadal Pacific Oscillation (IPO), El Niño/Southern Oscillation (ENSO) and changes in the location and strength of the westerlies as seen in the Southern Annular Mode (SAM). Along with mean warming of 0.8°C since 1900, a negative phase of the IPO, La Niña phase of ENSO and a strongly positive SAM contributed to five compound warm extremes in the extended austral summer seasons (NDJFM) of 1934/35, 2017/18, 2018/19, 2021/22 and 2022/23. These are the most intense coupled ocean/atmosphere (MHWs/AHWs) heatwaves on record with average temperature anomalies over land and sea +0.8°C to 1.1°C above 1991–2020 averages. The number of days above 25°C and above the 90th percentile of maximum temperature has increased, while the number of nights below 0°C and below the 10th percentile has decreased. Coastal waters around NZ recently experienced their longest MHW in the satellite era (1982‐present) of 289 days through 2023. The estimated recurrence interval reduces from 1 in 300‐years for the AHW event during the 1930s climate to a 1 in 25‐year event for the most recent decade. Consequences include major loss of ice of almost one‐third volume from Southern Alps glaciers from 2017 to 2021 with rapid melt of seasonal snow in all four cases. Above‐average temperatures in the December/January grape flowering period resulted in advances in veraison (the onset of ripening); and higher‐than‐average grape yields in 2022 and 2023 vintages. Marine impacts include widespread sea‐sponge bleaching around northern and southern NZ.

Trends in pancreatic cancer mortality in the United States 1999–2020: a CDC database population-based study - Alexander J. Didier; Swamroop Nandwani; Alan M. Fahoury; Daniel J. Craig; Dean Watkins; Andrew Campbell; Caleb T. Spencer; Macelyn Batten; Divya Vijendra; Jeffrey M. Sutton (Cancer Causes & Control, 2024)
Introduction Pancreatic cancer is a significant public health concern and a leading cause of cancer-related deaths worldwide. This study aimed to investigate pancreatic cancer mortality trends and disparities in the United States (US) from 1999 to 2020. Methods Data were obtained from the Centers for Disease Control (CDC) Wide-Ranging Online Data for Epidemiologic Research database. Mortality rates were age-adjusted and standardized to the year 2000 US population. Joinpoint regression was used to analyze temporal trends in age-adjusted mortality rates (AAMRs) by sociodemographic and geographic variables. Results Between 1999 and 2020, pancreatic cancer led to a total of 810,628 deaths in the US, an average mortality of nearly 39,000 deaths per year. The AAMR slightly increased from 10.6 in 1999 to 11.1 in 2020, with an associated annual percent change (APC) of 0.2. Mortality rates were highest among individuals aged 65 and older. Black individuals experienced the highest overall pancreatic cancer-related AAMR at 13.8. Despite this, Black individuals experienced a decreasing mortality trend over time (APC −0.2) while White individuals experienced an increasing trend in mortality (APC 0.4). Additionally, individuals residing in rural areas experienced steeper rates of mortality increase than those living in urban areas (APC 0.6 for rural vs −0.2 for urban). White individuals in urban and rural populations experienced an increase in mortality, while Black individuals in urban environments experienced a decrease in mortality, and Black individuals in rural environments experienced stable mortality trends. Conclusions Mortality from pancreatic cancer continues to increase in the US, with racial and regional disparities identified in minorities and rural-dwelling individuals. These disparate findings highlight the importance of ongoing efforts to understand and address pancreatic cancer treatment and outcomes disparities in the US, and future studies should further investigate the underlying etiologies of these disparities and potential for novel therapies to reduce the mortality.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Improving impact assessments to reduce impacts of deep-sea fisheries on vulnerable marine ecosystems - Laura Kaikkonen; Teresa Amaro; Peter J. Auster; David M. Bailey; James B. Bell; Angelika Brandt; Malcolm R. Clark; Jeffrey C. Drazen; Cherisse Du Preez; Elva Escobar-Briones; Eva Giacomello; Matthew Gianni; et al. (Marine Policy, 2024)

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

Spatiotemporal analysis provides solutions to mitigate bycatch of southern Gulf of St. Lawrence Atlantic Cod in an expanding Redfish fishery - Jolene T. Sutton; Jenni L. McDermid; Lysandre Landry; François Turcotte (Fisheries Research, 2024)

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

Changes in Cancer Screening Knowledge Among a Prospective Cohort of Spanish-Speaking Hispanic Community Outreach Event Participants in Florida and Puerto Rico - Shannon M. Christy; Eida M. Castro-Figueroa; Jomar Lopez; Steven K. Sutton; McKenzie McIntyre; Jennifer Garcia; Cynthia Cortes; Arline Vela Vidal; Clement K. Gwede; Melissa Marzán; Julio Jimenez; Susan T. Vadaparampil (Journal of Cancer Education, 2024)

Differential larval growth strategies and trophodynamics of larval Atlantic bluefin tuna (Thunnus thynnus) from two discrete spawning grounds - Estrella Malca; José M. Quintanilla; Trika Gerard; Francisco Alemany; Tracey Sutton; Alberto García; John T. Lamkin; Raúl Laiz-Carrión (Frontiers in Marine Science, 2023)
Atlantic bluefin tuna (ABT), Thunnus thynnus , is a globally important fishery resource. This oceanic top predator undertakes long-distance migrations from its nutrient-rich feeding grounds in the north Atlantic to oligotrophic spawning grounds. Larvae are born mainly in the corresponding ecosystems of its two well-established spawning areas: the Gulf of Mexico (GoM) and the Mediterranean Sea (MED). Stable isotopes analyses (SIA) of δ 15 N and δ 13 C have proven useful for understanding marine food webs and have evaluated larval ABT signatures in their respective spawning areas. This study is among the first to use larvae collected during the same spawning season (2014) from the GoM and one of the main spawning areas within the MED (the Balearic Sea) to standardize methodologies, compare larval growth, and relate SIA with larval postflexion growth using GAMs for the two spawning areas. The main findings identify significant population differences, with comparatively faster growth in GoM larvae. The GoM population had larger otoliths with wider increments, as well as higher δ 15 N values and higher trophic position for postflexion stages. Collectively, these findings highlight the importance of not only developing well-calibrated growth curves, but also integrating the distinct early life history dynamics for each spawning area to properly support ABT’s ongoing management efforts.

Cetacean‐mediated vertical nitrogen transport in the oceanic realm - Matthew S. Woodstock; Jeremy J. Kiszka; M. Rafael Ramírez‐León; Tracey T. Sutton; Katja Fennel; Bin Wang; Yuying Zhang (Limnology and Oceanography, 2023)
In natural systems, animal‐mediated nutrient transport can be a major driver of primary productivity, but the role of marine megafauna such as cetaceans in mediating the transfer and recycling of nutrients has been overlooked. Here, we developed a spatially resolved, stochastic, nutrient‐transport model for cetaceans in the oceanic Gulf of Mexico using species−specific foraging depths, distributions, and diets. An estimated 6.4 × 10 8 mmol N d −1 , or 0.06 mt N yr −1 ind −1 , is transported to the surface from depths below 100 m by the 19 cetacean species that occur in the oceanic Gulf of Mexico; 75% of this transport occurs seaward of the continental slope, but the per area transported nitrogen is greater on the continental slope (200–1000 m) than in the ocean basin. Benthos to surface transport comprised 6.0 × 10 7 mmol N d −1 and was much more common on the continental slope than the open basin. Compared to an existing physical‐biogeochemical model, the transported nutrients add 8% N d −1 to the estimated ammonium concentration above the nutricline and could add 16% N d −1 to the surface ammonium concentration if expelled nutrients remain at the surface. Through feeding on diel vertical migrants, cetaceans retain an additional 2.7 × 10 7 mmol N d −1 in the surface waters that would otherwise return to depth via downward diel vertical migration. Cetaceans contribute to nutrient movements and recycling in the oceanic Gulf of Mexico, and may provide one of the few allochthonous sources of nutrients for primary producers in oligotrophic ecosystems.

Measures and models of visual acuity in epipelagic and mesopelagic teleosts and elasmobranchs - Eleanor M. Caves; Tracey T. Sutton; Eric J. Warrant; Sönke Johnsen (Journal of Comparative Physiology A, 2023)
Eyes in low-light environments typically must balance sensitivity and spatial resolution. Vertebrate eyes with large "pixels" (e.g., retinal ganglion cells with inputs from many photoreceptors) will be sensitive but provide coarse vision. Small pixels can render finer detail, but each pixel will gather less light, and thus have poor signal relative-to-noise, leading to lower contrast sensitivity. This balance is particularly critical in oceanic species at mesopelagic depths (200–1000 m) because they experience low light and live in a medium that significantly attenuates contrast. Depending on the spatial frequency and inherent contrast of a pattern being viewed, the viewer’s pupil size and temporal resolution, and the ambient light level and water clarity, a visual acuity exists that maximizes the distance at which the pattern can be discerned. We develop a model that predicts this acuity for common conditions in the open ocean, and compare it to visual acuity in marine teleost fishes and elasmobranchs found at various depths in productive and oligotrophic waters. Visual acuity in epipelagic and upper mesopelagic species aligned well with model predictions, but species at lower mesopelagic depths (> 600 m) had far higher measured acuities than predicted. This is consistent with the prediction that animals found at lower mesopelagic depths operate in a visual world consisting primarily of bioluminescent point sources, where high visual acuity helps localize targets of this kind. Overall, the results suggest that visual acuity in oceanic fish and elasmobranchs is under depth-dependent selection for detecting either extended patterns or point sources.

Microplastic ingestion by deep‐pelagic crustaceans and fishes - Ryan P. Bos; Shiye Zhao; Tracey T. Sutton; Tamara M. Frank (Limnology and Oceanography, 2023)
A size‐selective loss of smaller microplastics ( −3 ) and cellophane (density 1.42 g cm −3 ) were mainly consumed. Our data indicate that nonmigratory crustaceans had significantly higher levels of microplastic ingestion than migratory crustaceans at all depths available for comparison. While migratory fishes ingested microplastics at higher frequencies (0.28) than nonmigratory fishes (0.23), the frequency of microplastic ingestion by nonmigratory fishes increased with depth and was highest at depths of 1200–1500 m (0.40). Paired with the data for crustaceans, these observations suggest that plastic ingestion may be higher at deeper depths. Feeding strategy also appeared correlated to microplastic ingestion, as species that rely on gelatinous materials and marine snow for energy had the highest levels of ingestion. Altogether, our data highlight a largely undescribed temporary reservoir and implicate important biological transport pathways for the smaller plastic size fractions in the open ocean.

Vulnerability and resilience of living marine resources to the Deepwater Horizon oil spill: an overview - Steven A. Murawski; Patrick T. Schwing; William F. Patterson; Tracey T. Sutton; Paul A. Montagna; Rosanna J. Milligan; Samantha B. Joye; Len Thomas; Joshua P. Kilborn; Claire B. Paris; Robin Faillettaz; David S. Portnoy; et al. (Frontiers in Marine Science, 2023)
The 2010 Deepwater Horizon (DWH) oil well blowout in the Gulf of Mexico (GoM) was the largest and perhaps most consequential accidental marine oil spill in global history. This paper provides an overview of a Research Topic consisting of four additional papers that: (1) assemble time series data for ecosystem components in regions impacted by the spill, and (2) interpret temporal changes related to the vulnerability of species and ecosystems to DWH and the ensuing resilience to perturbation. Time series abundance data for many taxa pre-date DWH, often by decades, thus allowing an assessment of population- and community-level impacts. We divided the north central GoM into four interconnected “eco-types”: the coastal/nearshore, continental shelf, open-ocean pelagic and deep benthic. Key taxa in each eco-type were evaluated for their vulnerability to the circumstances of the DWH spill based on population overlap with oil, susceptibility to oil contamination, and other factors, as well their imputed resilience to population-level impacts, based on life history metrics, ecology and post-spill trajectories. Each taxon was scored as low, medium, or high for 13 vulnerability attributes and 11 resilience attributes to produce overall vulnerability and resilience scores, which themselves were also categorical (i.e., low, medium, or high). The resulting taxon-specific V-R scores provide important guidance on key species to consider and monitor in the event of future spills similar to DWH. Similar analyses may also guide resource allocation to collect baseline data on highly vulnerable taxa or those with low resilience potential in other ecosystems. For some species, even a decade of observation has been insufficient to document recovery given chronic, long-term exposure to DWH oil remaining in all eco-types and because of impacts to the reproductive output of long-lived species. Due to the ongoing threats of deep-water blowouts, continued surveillance of populations affected by DWH is warranted to document long-term recovery or change in system state. The level of population monitoring in the open-ocean and deep benthic eco-types has historically been low and is inconsistent with the continued migration of the oil industry to the ultra-deep (≥1,500 m) where the majority of leasing, exploration, and production now occurs.

Ecomorphology of a predatory deep-sea fish family: does trophic specialization drive hyperspeciation? - Ryan P. McGonagle; David W. Kerstetter; Danté Fenolio; Tracey T. Sutton (Frontiers in Marine Science, 2023)
Two of the main drivers of speciation among aquatic vertebrates are physical isolation (e.g., lakes and streams) and micro-niche availability (e.g., tropical reefs). In both regards, the mesopelagic domain of the open ocean, Earth’s second largest cumulative ecosystem (behind only the bathypelagic domain), would seem retardant. Ocean circulation makes isolation rare on both contemporary and geological time/space scales, and the lack of substrate precludes stable micro-niches. Paradoxically, some pelagic taxa demonstrate much higher-than-expected species richness on regional scales. A prime example is the dragonfish family Stomiidae, the most speciose family of mesopelagic fishes, owing largely to the subfamily Melanostomiinae (scaleless black dragonfishes), which contributes 222 of the 320 described species. Within genera, species are differentiated almost solely by form of the jugular-positioned, bioluminescent barbel, a structure putatively linked to feeding (via prey luring). The relationship between diversity (both systematic and morphological) and diet within the Melanostomiinae has not been previously examined, primarily due to sample size limitation. Herein, the diet and morphology of 16 species of melanostomiine dragonfishes from the Gulf of Mexico were examined to ascertain whether the diversification in this fish clade is based on prey specialization, as is the case with many other speciose fish families (e.g., Cichlidae). Gut content analysis revealed a rather small spectrum of prey taxa across a wide spectrum of predators, with most species exhibiting piscivory centered on the most regionally abundant lanternfishes (Myctophidae). Lesser numbers of species preyed upon bristlemouths (Gonostomatidae), oceanic basslets (Howellidae), bigscales (Melamphaidae), and other dragonfishes, while three species selected for cephalopod prey. No dragonfish species consumed macrocrustaceans (e.g., decapod shrimps), despite their numerical prevalence as potential prey. Regarding functional morphology, dissimilarity was driven mostly by barbel length, vertical oral gape, and horizontal maxillary oral gape. There were no robust morphological-dietary relationships amongst melanostomiines, with dietary diversity much lower than morphological diversity. These results suggest that other factors, perhaps conspecific recognition and/or sexual selection related to spawning, may be primary drivers of hyperspeciation in the micro-habitat-poor pelagic environment.

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Body size, depth of occurrence, and local oceanography shape trophic structure in a diverse deep-pelagic micronekton assemblage - Travis M. Richards; Tracey T. Sutton; Matthew S. Woodstock; Heather Judkins; R.J. David Wells (Progress in Oceanography, 2023)

Decadal trends in surface solar radiation and cloud cover over the North Atlantic sector during the last four decades: drivers and physical processes - Buwen Dong; Rowan T. Sutton; Laura J. Wilcox (Climate Dynamics, 2023)
Satellite-derived products and reanalyses show consistent increases in downward surface solar radiation (SSR) and decreases in cloud cover over North America and Europe from the 1980s to 2010s. These trends show a strong seasonality, with the largest changes in boreal summer. A set of timeslice experiments with an atmospheric general circulation model (AGCM) forced with prescribed changes in sea surface temperature/sea ice extent (SST/SIE), greenhouse gas (GHG) concentrations, and anthropogenic aerosol (AA) emissions, together and separately, is performed to assess the relative roles of different forcings in these observed trends. The model reproduces the main observed features over Europe and North America, including the seasonality of trends, suggesting a dominant role of forced changes in the recent trends in SSR and cloud cover. Responses to individual forcings indicate that recent decadal trends in SSR over Europe are predominantly driven by AA emission reductions, with an additional influence from SST/SIE and GHG changes. In contrast, changes in AA, SST/SIE, and GHG contribute more equally to simulated decadal trends in SSR and cloud cover over North America, although SST/SIE play the most important role. In our simulations, responses of SSR to AA emission reductions are primarily governed by aerosol-radiation interactions. Responses to SST/SIE and GHG changes are predominantly due to cloud cover changes, which are driven by atmospheric circulation and humidity changes. This process level understanding of how different forcing factors influence decadal trends in SSR and cloud cover is valuable for understanding past changes and future projections in global and regional surface energy budgets, surface warming, and global and regional hydrological cycles.

Corrigendum: A trait‐based carbon export model for mesopelagic fishes in the Gulf of Mexico with consideration of asynchronous vertical migration, flux boundaries, and feeding guilds - Matthew S. Woodstock; Tracey T. Sutton; Yuying Zhang (Limnology and Oceanography, 2022)

GeoSoilEnviroCARS (Sector 13) at the Advanced Photon Source: a comprehensive synchrotron radiation facility for Earth science research at ambient and extreme conditions - S. R. Sutton; M. L. Rivers; S. Chariton; P. J. Eng; A. Lanzirotti; M. Newville; T. Officer; V. B. Prakapenka; Y. J. Ryu; J. E. Stubbs; S. Tkachev; Y. Wang; et al. (Physics and Chemistry of Minerals, 2022)

A trait‐based carbon export model for mesopelagic fishes in the Gulf of Mexico with consideration of asynchronous vertical migration, flux boundaries, and feeding guilds - Matthew S. Woodstock; Tracey T. Sutton; Yuying Zhang (Limnology and Oceanography, 2022)
Fish‐mediated carbon export provides a significant proportion of the biological carbon pump in oligotrophic regions. Bioenergetic models estimate this carbon transport, but many lack species‐specific traits and no carbon export model has been developed in the mesopelagic Gulf of Mexico. Intensive mesopelagic sampling efforts in the northern and eastern Gulf of Mexico have provided high‐resolution information regarding community composition, species' vertical migratory characteristics, diel depth occupancies, and diets. A stochastic, individual‐based model was developed for deep‐pelagic fishes in the northern Gulf of Mexico to estimate bioenergetic rates and carbon export fluxes. Fishes that ate gelatinous zooplankton consumed more mass per body weight per day than predators of cephalopods and fishes, ostensibly to increase the throughput of prey with less carbon (gelata) or more refractory materials (Crustacea). A dynamic energy budget submodel indicated that during 81% of occurrences, asynchronous vertically migrating fishes rested for 1 d before migrating again, but migrations on successive days were possible. In terms of carbon export, myctophids and stomiids contributed greater than 53% and 12% of the active carbon flux for the entire assemblage in all scenarios. The assemblage‐wide carbon export rate driven by vertically migrating fishes was 0.14–0.72 mg C m −2 d −1 , 61% of the ingested carbon by the assemblage. Incorporating species‐specific traits and individual variability in bioenergetic models allows for more complex research questions (e.g., the effect of feeding guilds and asynchronous migration on carbon export) compared to the carbon export models that otherwise assume all fishes within a functional group are equivalent.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Effects of environmental variables on a nearshore arctic fish community, 2001–2018 - J. T. Priest; F. J. Mueter; S. W. Raborn; T. M. Sutton (Polar Biology, 2022)

The genetics of vigour-related traits in chickpea (Cicer arietinum L.): insights from genomic data - Duong T. Nguyen; Julie E. Hayes; Judith Atieno; Yongle Li; Ute Baumann; Angela Pattison; Helen Bramley; Kristy Hobson; Manish Roorkiwal; Rajeev K. Varshney; Timothy D. Colmer; Tim Sutton (Theoretical and Applied Genetics, 2022)

Moving from trends to benchmarks by using regression tree analysis to find inbreeding thresholds in a critically endangered bird - Alison M. Flanagan; Bryce Masuda; Catherine E. Grueber; Jolene T. Sutton (Conservation Biology, 2021)
Understanding how inbreeding affects endangered species in conservation breeding programs is essential for their recovery. The Hawaiian Crow (‘Alalā) ( Corvus hawaiiensis ) is one of the world's most endangered birds. It went extinct in the wild in 2002, and, until recent release efforts starting in 2016, nearly all of the population remained under human care for conservation breeding. Using pedigree inbreeding coefficients ( F ), we evaluated the effects of inbreeding on Hawaiian Crow offspring survival and reproductive success. We used regression tree analysis to identify the level of inbreeding (i.e., inbreeding threshold) that explains a substantial decrease in ‘Alalā offspring survival to recruitment. Similar to a previous study of inbreeding in ‘Alalā, we found that inbreeding had a negative impact on offspring survival but that parental (vs. artificial) egg incubation improved offspring survival to recruitment. Furthermore, we found that inbreeding did not substantially affect offspring reproductive success, based on the assumption that offspring that survive to adulthood breed with distantly related mates. Our novel application of regression tree analysis showed that offspring with inbreeding levels exceeding F = 0.098 were 69% less likely to survive to recruitment than more outbred offspring, providing a specific threshold value for ongoing population management. Our results emphasize the importance of assessing inbreeding depression across all life history stages, confirm the importance of prioritizing parental over artificial egg incubation in avian conservation breeding programs, and demonstrate the utility of regression tree analysis as a tool for identifying inbreeding thresholds, if present, in any pedigree‐managed population.

Editorial: Deep Pelagic Ecosystem Dynamics in a Highly Impacted Water Column: The Gulf of Mexico After Deepwater Horizon - Tracey T. Sutton; Kevin M. Boswell; Heather D. Bracken-Grissom; Jose V. Lopez; Michael Vecchione; Marsh Youngbluth (Frontiers in Marine Science, 2021)

Men’s experiences of radiotherapy treatment for localized prostate cancer and its long-term treatment side effects: a longitudinal qualitative study - E. Sutton; J. A. Lane; M. Davis; E. I. Walsh; D. E. Neal; F. C. Hamdy; M. Mason; J. Staffurth; R. M. Martin; C. Metcalfe; T. J. Peters; J. L. Donovan; et al. (Cancer Causes & Control, 2021)
Purpose To investigate men’s experiences of receiving external-beam radiotherapy (EBRT) with neoadjuvant Androgen Deprivation Therapy (ADT) for localized prostate cancer (LPCa) in the ProtecT trial. Methods A longitudinal qualitative interview study was embedded in the ProtecT RCT. Sixteen men with clinically LPCa who underwent EBRT in ProtecT were purposively sampled to include a range of socio-demographic and clinical characteristics. They participated in serial in-depth qualitative interviews for up to 8 years post-treatment, exploring experiences of treatment and its side effects over time. Results Men experienced bowel, sexual, and urinary side effects, mostly in the short term but some persisted and were bothersome. Most men downplayed the impacts, voicing expectations of age-related decline, and normalizing these changes. There was some reticence to seek help, with men prioritizing their relationships and overall health and well-being over returning to pretreatment levels of function. Some unmet needs with regard to information about treatment schedules and side effects were reported, particularly among men with continuing functional symptoms. Conclusions These findings reinforce the importance of providing universal clear, concise, and timely information and supportive resources in the short term, and more targeted and detailed information and care in the longer term to maintain and improve treatment experiences for men undergoing EBRT.

State of Satiation Partially Regulates the Dynamics of Vertical Migration - Ryan P. Bos; Tracey T. Sutton; Tamara M. Frank (Frontiers in Marine Science, 2021)
Vertical migrations into shallower waters at night are beneficial for migrators as they reduce predation risk and allow migrators to encounter a higher density of prey. Nevertheless, ocean acoustics data and trawl data have shown that a portion of some vertically migrating populations remain at depth and do not migrate. One hypothesis for this phenomenon is the Hunger-Satiation hypothesis, which in part states that the non-migrating portion of the migrating species-assemblage refrains from migrating if they have full or partially full stomachs from daytime or nocturnal feeding. However, stomach fullness of the non-migrating subpopulation compared to the migrating portion has rarely been studied, due to the difficulty in obtaining sufficient samples. The stomach fullness levels of numerically abundant crustacean and fish species with well-known depth distributions were quantified in the present study. Animals were captured during night trawls from discrete-depth intervals between 0 and 1,500 m. Stomach fullness indices were assigned from 0 to 5 and compared between migratory taxa caught in shallow and deep waters. Data from the crustaceans Acanthephyra purpurea, Gardinerosergia splendens, Plesionika richardi , and Systellaspsis debilis , as well as the fishes Lampanyctus alatus, Lepidophanes guentheri , and Notolychnus valdiviae , provided support for the Hunger-Satiation hypothesis, while data from the crustaceans Gennadas capensis and Gennadas valens and the fish Benthosema suborbitale did not. These findings suggest that stomach vacancy may be just one of several factors regulating the dynamics of vertical migration in those species whose behavioral plasticity suggests daily “choices” in whether or not to vertically migrate.

Microscopic and Genetic Characterization of Bacterial Symbionts With Bioluminescent Potential in Pyrosoma atlanticum - Alexis Berger; Patricia Blackwelder; Tamara Frank; Tracey T. Sutton; Nina M. Pruzinsky; Natalie Slayden; Jose V. Lopez (Frontiers in Marine Science, 2021)
The pelagic tunicate pyrosome, Pyrosoma atlanticum , is known for its brilliant bioluminescence, but the mechanism causing this bioluminescence has not been fully characterized. This study identifies the bacterial bioluminescent symbionts of P. atlanticum collected in the northern Gulf of Mexico using several methods such as light and electron microscopy, as well as molecular genetics. The bacteria are localized within the pyrosome light organs. Greater than 50% of the bacterial taxa present in the tunicate samples were the bioluminescent symbiotic bacteria Vibrionaceae as determined by utilizing current molecular genetics methodologies. A total of 396K MiSeq16S rRNA reads provided total pyrosome microbiome profiles to determine bacterial symbiont taxonomy. After comparing with the Silva rRNA database, a Photobacterium sp. r33-like bacterium (which we refer to as “ Photobacterium Pa-1”) matched at 99% sequence identity as the most abundant bacteria within Pyrosoma atlanticum samples. Specifically designed 16S rRNA V4 probes for fluorescence in situ hybridization (FISH) verified the Photobacterium Pa-1 location as internally concentrated along the periphery of each dual pyrosome luminous organ. While searching for bacterial lux genes in two tunicate samples, we also serendipitously generated a draft tunicate mitochondrial genome that can be used for Pyrosoma atlanticum identification. Scanning (SEM) and transmission (TEM) electron microscopy confirmed the presence of intracellular rod-like bacteria in the light organs. This intracellular localization of bacteria may represent bacteriocyte formation reminiscent of other invertebrates.

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

Diet and parasites of a mesopelagic fish assemblage in the Gulf of Mexico - Matthew S. Woodstock; Christopher A. Blanar; Tracey T. Sutton (Marine Biology, 2020)

Trophic Structure and Sources of Variation Influencing the Stable Isotope Signatures of Meso- and Bathypelagic Micronekton Fishes - Travis M. Richards; Tracey T. Sutton; R. J. David Wells (Frontiers in Marine Science, 2020)

Using structured eradication feasibility assessment to prioritize the management of new and emerging invasive alien species in Europe - Olaf Booy; Pete A. Robertson; Niall Moore; Jess Ward; Helen E. Roy; Tim Adriaens; Richard Shaw; Johan Van Valkenburg; Gabrielle Wyn; Sandro Bertolino; Olivier Blight; Etienne Branquart; et al. (Global Change Biology, 2020)
Prioritizing the management of invasive alien species (IAS) is of global importance and within Europe integral to the EU IAS regulation. To prioritize management effectively, the risks posed by IAS need to be assessed, but so too does the feasibility of their management. While the risk of IAS to the EU has been assessed, the feasibility of management has not. We assessed the feasibility of eradicating 60 new (not yet established) and 35 emerging (established with limited distribution) species that pose a threat to the EU, as identified by horizon scanning. The assessment was carried out by 34 experts in invasion management from across Europe, applying the Non‐Native Risk Management scheme to defined invasion scenarios and eradication strategies for each species, assessing the feasibility of eradication using seven key risk management criteria. Management priorities were identified by combining scores for risk (derived from horizon scanning) and feasibility of eradication. The results show eradication feasibility score and risk score were not correlated, indicating that risk management criteria evaluate different information than risk assessment. In all, 17 new species were identified as particularly high priorities for eradication should they establish in the future, whereas 14 emerging species were identified as priorities for eradication now. A number of species considered highest priority for eradication were terrestrial vertebrates, a group that has been the focus of a number of eradication attempts in Europe. However, eradication priorities also included a diverse range of other taxa (plants, invertebrates and fish) suggesting there is scope to broaden the taxonomic range of attempted eradication in Europe. We demonstrate that broad scale structured assessments of management feasibility can help prioritize IAS for management. Such frameworks are needed to support evidence‐based decision‐making.

Knowledge Gaps and Management Priorities for Recreational Fisheries in the Developing World - Shannon D. Bower; Øystein Aas; Robert Arlinghaus; T. Douglas Beard; Ian G. Cowx; Andy J. Danylchuk; Kátia M. F. Freire; Warren M. Potts; Stephen G. Sutton; Steven J. Cooke (Reviews in Fisheries Science & Aquaculture, 2020)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Attribution of 2012 extreme climate events: does air-sea interaction matter? - Buwen Dong; Rowan T. Sutton; Len Shaffrey; Laura J. Wilcox (Climate Dynamics, 2020)
In 2012, extreme anomalous climate conditions occurred around the globe. Large areas of North America experienced an anomalously hot summer, with large precipitation deficits inducing severe drought. Over Europe, the summer of 2012 was marked by strong precipitation anomalies with the UK experiencing its wettest summer since 1912 while Spain suffered severe drought. What caused these extreme climate conditions in various regions in 2012? This study compares attribution conclusions for 2012 climate anomalies relative to a baseline period (1964–1981) based on two sets of parallel experiments with different model configurations (with coupling to an ocean mixed layer model or with prescribed sea surface temperatures) to assess whether attribution conclusions concerning the climate anomalies in 2012 are sensitive to the representation of air-sea interaction. Modelling results indicate that attribution conclusions for large scale surface air temperature (SAT) changes in both boreal winter and summer are generally robust and not very sensitive to air-sea interaction. This is especially true over southern Europe, Eurasia, North America, South America, and North Africa. Some other responses also appear to be insensitive to air-sea interaction: for example, forced increases in precipitation over northern Europe and Sahel, and reduced precipitation over North America and the Amazon in boreal summer. However, the attribution of circulation and precipitation changes for some other regions exhibits a sensitivity to air-sea interaction. Results from the experiments including coupling to an ocean mixed layer model show a positive NAO-like circulation response in the Atlantic sector in boreal winter and weak changes in the East Asian summer monsoon and precipitation over East Asia. With prescribed sea surface temperatures, some different responses arise over these two regions. Comparison with observed changes indicates that the coupled simulations generally agree better with observations, demonstrating that attribution methods based on atmospheric general circulation models have limitations and may lead to erroneous attribution conclusions for regional anomalies in circulation, precipitation and surface air temperature.

Unparalleled coupled ocean-atmosphere summer heatwaves in the New Zealand region: drivers, mechanisms and impacts - M. James Salinger; Howard J. Diamond; Erik Behrens; Denise Fernandez; B. Blair Fitzharris; Nicholas Herold; Paul Johnstone; Huub Kerckhoffs; A. Brett Mullan; Amber K. Parker; James Renwick; Claire Scofield; et al. (Climatic Change, 2020)

Taxonomic Richness and Diversity of Larval Fish Assemblages in the Oceanic Gulf of Mexico: Links to Oceanographic Conditions - Corinne R. Meinert; Kimberly Clausen-Sparks; Maëlle Cornic; Tracey T. Sutton; Jay R. Rooker (Frontiers in Marine Science, 2020)

Hiding in Plain Sight: Elopomorph Larvae Are Important Contributors to Fish Biodiversity in a Low-Latitude Oceanic Ecosystem - Jon A. Moore; Dante B. Fenolio; April B. Cook; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Pelagic Habitat Partitioning of Late-Larval and Juvenile Tunas in the Oceanic Gulf of Mexico - Nina M. Pruzinsky; Rosanna J. Milligan; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Reproductive Ecology of Dragonfishes (Stomiiformes: Stomiidae) in the Gulf of Mexico - Alex D. Marks; David W. Kerstetter; David M. Wyanski; Tracey T. Sutton (Frontiers in Marine Science, 2020)

The Vertical and Horizontal Distribution of Deep-Sea Crustaceans in the Order Euphausiacea in the Vicinity of the DeepWater Horizon Oil Spill - Tamara M. Frank; Charles D. Fine; Eric A. Burdett; April B. Cook; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Oceanographic Structure and Light Levels Drive Patterns of Sound Scattering Layers in a Low-Latitude Oceanic System - Kevin M. Boswell; Marta D’Elia; Matthew W. Johnston; John A. Mohan; Joseph D. Warren; R. J. David Wells; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Dispersion Overrides Environmental Variability as a Primary Driver of the Horizontal Assemblage Structure of the Mesopelagic Fish Family Myctophidae in the Northern Gulf of Mexico - Rosanna J. Milligan; Tracey T. Sutton (Frontiers in Marine Science, 2020)

Virtual time-to-contact identifies balance deficits better than traditional metrics in people with multiple sclerosis - Tyler T. Whittier; Sutton B. Richmond; Andrew S. Monaghan; Brett W. Fling (Experimental Brain Research, 2020)

A standardized method for the construction of a tick drag/flag sampling approach and evaluation of sampling efficacy - Brent C. Newman; William B. Sutton; Yong Wang; Callie J. Schweitzer; Abelardo C. Moncayo; Brian T. Miller (Experimental and Applied Acarology, 2019)

Impacts of recent decadal changes in Asian aerosols on the East Asian summer monsoon: roles of aerosol–radiation and aerosol–cloud interactions - Buwen Dong; Laura J. Wilcox; Eleanor J. Highwood; Rowan T. Sutton (Climate Dynamics, 2019)

Public–Private Partnerships to Advance Regional Ocean-Observing Capabilities: A Saildrone and NOAA-PMEL Case Study and Future Considerations to Expand to Global Scale Observing - Christian Meinig; Eugene F. Burger; Nora Cohen; Edward D. Cokelet; Meghan F. Cronin; Jessica N. Cross; Sebastien de Halleux; Richard Jenkins; Andrew T. Jessup; Calvin W. Mordy; Noah Lawrence-Slavas; Adrienne J. Sutton; et al. (Frontiers in Marine Science, 2019)

Variation in rod spectral sensitivity of fishes is best predicted by habitat and depth - Lorian E. Schweikert; Eleanor M. Caves; Sarah E. Solie; Tracey T. Sutton; Sönke Johnsen (Journal of Fish Biology, 2019)
Rod spectral sensitivity data ( λ max ), measured by microspectrophotometry, were compiled for 403 species of ray‐finned fishes in order to examine four hypothesized predictors of rod spectral sensitivity (depth, habitat, diet and temperature). From this database, a subset of species that were known to be adults and available on a published phylogeny ( n = 210) were included in analysis, indicating rod λ max values averaging 503 nm and ranging from 477 to 541 nm. Linear models that corrected for phylogenetic relatedness showed that variation in rod sensitivity was best predicted by habitat and depth, with shorter wavelength λ max values occurring in fishes found offshore or in the deep sea. Neither diet, nor the interaction of diet and habitat, had significant explanatory power. Although temperature significantly correlated with rod sensitivity, in that fishes in temperate latitudes had longer wavelength rod λ max values than those in tropical latitudes, sampling inequity and other confounds require the role of the temperature to be studied further. Together, these findings indicate that fish rod λ max is influenced by several ecological factors, suggesting that selection can act on even small differences in fish spectral sensitivity.

The Tropical Atlantic Observing System - G. R. Foltz; P. Brandt; I. Richter; B. Rodríguez-Fonseca; F. Hernandez; M. Dengler; R. R. Rodrigues; J. O. Schmidt; L. Yu; N. Lefevre; L. Cotrim Da Cunha; M. J. McPhaden; et al. (Frontiers in Marine Science, 2019)
The tropical Atlantic is home to multiple coupled climate variations covering a wide range of timescales and impacting societally relevant phenomena such as continental rainfall, Atlantic hurricane activity, oceanic biological productivity, and atmospheric circulation in the equatorial Pacific. The tropical Atlantic also connects the southern and northern branches of the Atlantic meridional overturning circulation and receives freshwater input from some of the world’s largest rivers. To address these diverse, unique, and interconnected research challenges, a rich network of ocean observations has developed, building on the backbone of the Prediction and Research Moored Array in the Tropical Atlantic (PIRATA). This network has evolved naturally over time and out of necessity in order to address the most important outstanding scientific questions and to improve predictions of tropical Atlantic severe weather and global climate variability and change. The tropical Atlantic observing system is motivated by goals to understand and better predict phenomena such as tropical Atlantic interannual to decadal variability and climate change; multidecadal variability and its links to the meridional overturning circulation; air-sea fluxes of CO 2 and their implications for the fate of anthropogenic CO 2 ; the Amazon River plume and its interactions with biogeochemistry, vertical mixing, and hurricanes; the highly productive eastern boundary and equatorial upwelling systems; and oceanic oxygen minimum zones, their impacts on biogeochemical cycles and marine ecosystems, and their feedbacks to climate. Past success of the tropical Atlantic observing system is the result of an international commitment to sustained observations and scientific cooperation, a willingness to evolve with changing research and monitoring needs, and a desire to share data openly with the scientific community and operational centers. The observing system must continue to evolve in order to meet an expanding set of research priorities and operational challenges. This paper discusses the tropical Atlantic observing system, including emerging scientific questions that demand sustained ocean observations, the potential for further integration of the observing system, and the requirements for sustaining and enhancing the tropical Atlantic observing system.

Hawaii Coastal Seawater CO2 Network: A Statistical Evaluation of a Decade of Observations on Tropical Coral Reefs - Gerianne J. Terlouw; Lucie A. C. M. Knor; Eric Heinen De Carlo; Patrick S. Drupp; Fred T. Mackenzie; Yuan Hui Li; Adrienne J. Sutton; Albert J. Plueddemann; Christopher L. Sabine (Frontiers in Marine Science, 2019)

The Second Warning to Humanity – Providing a Context for Wetland Management and Policy - C. M. Finlayson; Gillian T. Davies; William R. Moomaw; G. L. Chmura; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2019)

Monitoring programs of the U.S. Gulf of Mexico: inventory, development and use of a large monitoring database to map fish and invertebrate spatial distributions - Arnaud Grüss; Holly A. Perryman; Elizabeth A. Babcock; Skyler R. Sagarese; James T. Thorson; Cameron H. Ainsworth; Evan John Anderson; Kenneth Brennan; Matthew D. Campbell; Mary C. Christman; Scott Cross; Michael D. Drexler; et al. (Reviews in Fish Biology and Fisheries, 2018)

Further spectral and chromatographic studies of ambergris - Steven J. Rowland; Paul A. Sutton; Simon T. Belt; Vera Fitzsimmons-Thoss; Alan G. Scarlett (Natural Product Research, 2018)

Restructuring of a mutualism following introduction of Australian fig trees and pollinating wasps to Europe and the USA - E. J. Morgan; T. L. Sutton; C. T. Darwell; J. M. Cook (Biological Invasions, 2018)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Physician Communication Practices as a Barrier to Risk-Based HPV Vaccine Uptake Among Men Who Have Sex with Men - Christopher W. Wheldon; Steven K. Sutton; Holly B. Fontenot; Gwendolyn P. Quinn; Anna R. Giuliano; Susan T. Vadaparampil (Journal of Cancer Education, 2018)

Comparison of Health Communication Channels for Reaching Hispanics About Biobanking: a Pilot Trial - Jessica McIntyre; Julio Jiménez; Yonaira M. Rivera; Steven K. Sutton; Gloria Asencio; Eida M. Castro-Figueroa; Clement K. Gwede; Thomas H. Brandon; Susan T. Vadaparampil; Vani N. Simmons; Johanna Corchado; Laura Moreno; et al. (Journal of Cancer Education, 2018)

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

Energy expenditure of rugby players during a 14-day in-season period, measured using doubly labelled water - Deborah R. Smith; R. F. G. J. King; L. C. Duckworth; L. Sutton; T. Preston; J. P. O’Hara; B. Jones (European Journal of Applied Physiology, 2018)

Global biogeochemical provinces of the mesopelagic zone - Gabriel Reygondeau; Lionel Guidi; Gregory Beaugrand; Stephanie A. Henson; Philippe Koubbi; Brian R. MacKenzie; Tracey T. Sutton; Martine Fioroni; Olivier Maury (Journal of Biogeography, 2018)
Aim Following the biogeographical approach implemented by Longhurst for the epipelagic layer, we propose here to identify a biogeochemical 3‐D partition for the mesopelagic layer. The resulting partition characterizes the main deep environmental biotopes and their vertical boundaries on a global scale, which can be used as a geographical and ecological framework for conservation biology, ecosystem‐based management and for the design of oceanographic investigations. Location The global ocean. Methods Based on the most comprehensive environmental climatology available to date, which is both spatially and vertically resolved (seven environmental parameters), we applied a combination of clustering algorithms (c‐means, k‐means, partition around medoids and agglomerative with Ward's linkage) associated with a nonparametric environmental model to identify the vertical and spatial delineation of the mesopelagic layer. Results First , we show via numerical interpretation that the vertical division of the pelagic zone varies and, hence, is not constant throughout the global ocean. Indeed, a latitudinal gradient is found between the epipelagic–mesopelagic and mesopelagic–bathypelagic vertical limits. Second, the mesopelagic layer is shown here to be composed of 13 distinguishable Biogeochemical Provinces. Each province shows a distinct range of environmental conditions and characteristic 3‐D distributions. Main conclusions The historical definition of the mesopelagic zone is here revisited to define a 3‐D geographical framework and characterize all the deep environmental biotopes of the deep global ocean. According to the numerical interpretation of mesopelagic boundaries, we reveal that the vertical division of the zone is not constant over the global ocean (200–1,000 m) but varies between ocean basin and with latitude. We also provide evidence of biogeochemical division of the mesopelagic zone that is spatially structured in a similar way than the epipelagic in the shallow waters but varies in the deep owing to a change of the environmental driving factors.

Erratum to: Understanding the rapid summer warming and changes in temperature extremes since the mid-1990s over Western Europe - Buwen Dong; Rowan T. Sutton; Len Shaffrey (Climate Dynamics, 2017)

Mechanisms of decadal variability in the Labrador Sea and the wider North Atlantic in a high-resolution climate model - Pablo Ortega; Jon Robson; Rowan T. Sutton; Martin B. Andrews (Climate Dynamics, 2017)

Diversity of midwater cephalopods in the northern Gulf of Mexico: comparison of two collecting methods - H. Judkins; M. Vecchione; A. Cook; T. Sutton (Marine Biodiversity, 2017)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.

Reciprocal translocation of small numbers of inbred individuals rescues immunogenetic diversity - Catherine E. Grueber; Jolene T. Sutton; Sol Heber; James V. Briskie; Ian G. Jamieson; Bruce C. Robertson (Molecular Ecology, 2017)
Genetic rescue can reduce inbreeding depression and increase fitness of small populations, even when the donor populations are highly inbred. In a recent experiment involving two inbred island populations of the New Zealand South Island robin, Petroica australis, reciprocal translocations improved microsatellite diversity and individual fitness. While microsatellite loci may reflect patterns of genome‐wide diversity, they generally do not indicate the specific genetic regions responsible for increased fitness. We tested the effectiveness of this reciprocal translocation for rescuing diversity of two immunogenetic regions: Toll‐like receptor ( TLR ) and major histocompatibility complex ( MHC ) genes. We found that the relatively small number of migrants (seven and ten per island) effectively brought the characteristic TLR gene diversity of each source population into the recipient population. However, when migrants transmitted TLR alleles that were already present at high frequency in the recipient population, it was possible for offspring of mixed heritage to have decreased gene diversity compared to recipient population diversity prior to translocation. In contrast to TLR s, we did not observe substantial changes in MHC allelic diversity following translocation, with limited evidence of a decrease in differentiation, perhaps because most MHC alleles were observed at both sites prior to the translocation. Overall, we conclude that small numbers of migrants may successfully restore the diversity of immunogenetic loci with few alleles, but that translocating larger numbers of animals would provide additional opportunity for the genetic rescue of highly polymorphic immunity regions, such as the MHC , even when the source population is inbred.

Distribution and ecology of lampreys Lethenteron spp. in interior Alaskan rivers - T. M. Sutton (Journal of Fish Biology, 2017)
This study describes phenetic characteristics and examines the life history of anadromous Arctic lamprey Lethenteron camtschaticum and freshwater‐resident Alaskan brook lamprey Lethenteron alaskense in two tributaries of the middle Yukon River, Alaska. Larval lampreys could not be identified to species using pigmentation density patterns or trunk myomere counts, but adults could be identified to species based on colouration, body size and oral‐disc dentition. Although larvae were patchily distributed in both rivers, there was a greater proportion of sample locations where Lethenteron spp. were absent in upper reaches than in middle and lower reaches. Relative abundance, density and median and maximum total length ( L T ) of larvae were highly variable among sampling locations. Current velocity, substratum type and coarse woody debris were most strongly correlated with larval Lethenteron spp. density; velocity and substratum size was negatively correlated, whereas woody debris was positively correlated. Water depth, dissolved oxygen levels and specific conductance did not influence habitat selection. Length–frequency distributions, diet composition (organic detritus ≥ 98%), assimilation efficiency (>70%) and gut fullness ( Lethenteron spp. biology and ecology in interior Alaska drainages and add to the existing literature on Lethenteron spp. life history.

Understanding the rapid summer warming and changes in temperature extremes since the mid-1990s over Western Europe - Buwen Dong; Rowan T. Sutton; Len Shaffrey (Climate Dynamics, 2017)

Decadal predictions with the HiGEM high resolution global coupled climate model: description and basic evaluation - L. C. Shaffrey; D. Hodson; J. Robson; D. P. Stevens; E. Hawkins; I. Polo; I. Stevens; R. T. Sutton; G. Lister; A. Iwi; D. Smith; A. Stephens (Climate Dynamics, 2017)

Abrupt summer warming and changes in temperature extremes over Northeast Asia since the mid-1990s: Drivers and physical processes - Buwen Dong; Rowan T. Sutton; Wei Chen; Xiaodong Liu; Riyu Lu; Ying Sun (Advances in Atmospheric Sciences, 2016)
This study investigated the drivers and physical processes for the abrupt decadal summer surface warming and increases in hot temperature extremes that occurred over Northeast Asia in the mid-1990s. Observations indicate an abrupt increase in summer mean surface air temperature (SAT) over Northeast Asia since the mid-1990s. Accompanying this abrupt surface warming, significant changes in some temperature extremes, characterized by increases in summer mean daily maximum temperature (Tmax), daily minimum temperature (Tmin), annual hottest day temperature (TXx), and annual warmest night temperature (TNx) were observed. There were also increases in the frequency of summer days (SU) and tropical nights (TR). Atmospheric general circulation model experiments forced by changes in sea surface temperature (SST)/sea ice extent (SIE), anthropogenic greenhouse gas (GHG) concentrations, and anthropogenic aerosol (AA) forcing, relative to the period 1964–93, reproduced the general patterns of observed summer mean SAT changes and associated changes in temperature extremes, although the abrupt decrease in precipitation since the mid-1990s was not simulated. Additional model experiments with different forcings indicated that changes in SST/SIE explained 76% of the area-averaged summer mean surface warming signal over Northeast Asia, while the direct impact of changes in GHG and AA explained the remaining 24% of the surface warming signal. Analysis of physical processes indicated that the direct impact of the changes in AA (through aerosol–radiation and aerosol–cloud interactions), mainly related to the reduction of AA precursor emissions over Europe, played a dominant role in the increase in TXx and a similarly important role as SST/SIE changes in the increase in the frequency of SU over Northeast Asia via AA-induced coupled atmosphere–land surface and cloud feedbacks, rather than through a direct impact of AA changes on cloud condensation nuclei. The modelling results also imply that the abrupt summer surface warming and increases in hot temperature extremes over Northeast Asia since the mid-1990s will probably sustain in the next few decades as GHG concentrations continue to increase and AA precursor emissions over both North America and Europe continue to decrease.

Recommendations for the future of recreational fisheries to prepare the social‐ecological system to cope with change - R. Arlinghaus; S. J. Cooke; S. G. Sutton; A. J. Danylchuk; W. Potts; K. de M. F. Freire; J. Alós; E. T. da Silva; I. G. Cowx; R. van Anrooy (Fisheries Management and Ecology, 2016)
This paper presents conclusions and recommendations that emerged from the 7th World Recreational Fishing Conference ( WRFC ) held in Campinas, Brazil in September 2014. Based on the recognition of the immense social and economic importance of recreational fisheries coupled with weaknesses in robust information about these fisheries in many areas of the world, particularly in many economies in transition, it is recommended to increase effort to build effective governance arrangements and improve monitoring and assessment frameworks in data‐poor situations. Moreover, there is a need to increase interdisciplinary studies that will foster a systematic understanding of recreational fisheries as complex adaptive social‐ecological systems. To promote sustainable recreational fisheries on a global scale, it is recommended the detailed suggestions for governance and management outlined in the United Nations Food and Agricultural Organization Technical Guidelines for Responsible Fisheries: Recreational Fisheries are followed.

Preferred response of the East Asian summer monsoon to local and non-local anthropogenic sulphur dioxide emissions - Buwen Dong; Rowan T. Sutton; Eleanor J. Highwood; Laura J. Wilcox (Climate Dynamics, 2016)

Quantifying alosine prey in the diets of marine piscivores in the Gulf of Maine - S. P. McDermott; N. C. Bransome; S. E. Sutton; B. E. Smith; J. S. Link; T. J. Miller (Journal of Fish Biology, 2015)
The objectives of this work were to quantify the spatial and temporal distribution of the occurrence of anadromous fishes (alewife Alosa pseudoharengus , blueback herring Alosa aestivalis and American shad Alosa sapidissima ) in the stomachs of demersal fishes in coastal waters of the north‐west Atlantic Ocean. Results show that anadromous fishes were detectable and quantifiable in the diets of common marine piscivores for every season sampled. Even though anadromous fishes were not the most abundant prey, they accounted for c. 5–10% of the diet by mass for several marine piscivores. Statistical comparisons of these data with fish diet data from a broad‐scale survey of the north‐west Atlantic Ocean indicate that the frequency of this trophic interaction was significantly higher within spatially and temporally focused sampling areas of this study than in the broad‐scale survey. Odds ratios of anadromous predation were as much as 460 times higher in the targeted sampling as compared with the broad‐scale sampling. Analyses indicate that anadromous prey consumption was more concentrated in the near‐coastal waters compared with consumption of a similar, but more widely distributed species, the Atlantic herring Clupea harengus . In the context of ecosystem‐based fisheries management, the results suggest that even low‐frequency feeding events may be locally important, and should be incorporated into ecosystem models.

MHC variation reflects the bottleneck histories of N ew Z ealand passerines - Jolene T. Sutton; Bruce C. Robertson; Ian G. Jamieson (Molecular Ecology, 2015)
Most empirical evidence suggests that balancing selection does not counter the effects of genetic drift in shaping postbottleneck major histocompatibility complex ( MHC ) genetic diversity when population declines are severe or prolonged. However, few studies have been able to include data from historical specimens, or to compare populations/species with different bottleneck histories. In this study, we examined MHC class II B and microsatellite diversity in four N ew Z ealand passerine (songbird) species that experienced moderate to very severe declines. We compared diversity from historical samples (collected c . 1884–1938) to present‐day populations. Using a Bayesian framework, we found that the change in genetic diversity from historical to contemporary samples was affected by three main factors: (i) whether the data were based on MHC or microsatellite markers, (ii) species (as a surrogate for bottleneck severity) and (iii) whether the comparison between historical and contemporary samples was made using historical samples originating from the mainland, or using historical samples originating from islands. The greatest losses in genetic diversity occurred for the most severely bottlenecked species, particularly between historical mainland and contemporary samples. Additionally, where loss of diversity occurred, the change was greater for MHC genes compared to microsatellite loci.

Simulation of CO2 and Attribution Analysis at Six European Peatland Sites Using the ECOSSE Model - M. Abdalla; A. Hastings; M. J. Bell; J. U. Smith; M. Richards; M. B. Nilsson; M. Peichl; M. O. Löfvenius; M. Lund; C. Helfter; E. Nemitz; M. A. Sutton; et al. (Water, Air, & Soil Pollution, 2014)

Summer Movements of the Gulf Killifish (Fundulus grandis) in a Northern Gulf of Mexico Salt Marsh - T. Reid Nelson; Deionta Sutton; Dennis R. DeVries (Estuaries and Coasts, 2014)

Vertical ecology of the pelagic ocean: classical patterns and new perspectives - T. T. Sutton (Journal of Fish Biology, 2013)
Applications of acoustic and optical sensing and intensive, discrete‐depth sampling, in concert with collaborative international research programmes, have substantially advanced knowledge of pelagic ecosystems in the 17 years since the 1996 Deepwater Fishes Symposium of the Fisheries Society of the British Isles. Although the epipelagic habitat is the best‐known, and remote sensing and high‐resolution modelling allow near‐synoptic investigation of upper layer biophysical dynamics, ecological studies within the mesopelagic and deep‐demersal habitats have begun to link lower and upper trophic level processes. Bathypelagic taxonomic inventories are far from complete, but recent projects ( e.g . MAR‐ECO and CMarZ , supported by the Census of Marine Life programme) have quantitatively strengthened distribution patterns previously described for fishes and have provided new perspectives. Synthesis of net and acoustic studies suggests that the biomass of deep‐pelagic fishes may be two to three orders of magnitude greater than the total global commercial fisheries landings. Discrete‐depth net sampling has revealed relatively high pelagic fish biomass below 1000 m in some regions, and that gelatinous zooplankton may be key energy vectors for deep‐pelagic fish production. Lastly, perhaps, the most substantive paradigm shift is that vertical connectivity among fishes across classical depth zones is prevalent– suggesting that a whole‐water column approach is warranted for deep ocean conservation and management.

Testing the Effects of Constraints on Climate Change–Friendly Behavior among Groups of Australian Residents - Jee In Yoon; Gerard T. Kyle; Carena J. van Riper; Stephen G. Sutton (Coastal Management, 2013)

Changes in tropical Atlantic interannual variability from a substantial weakening of the meridional overturning circulation - Irene Polo; Buwen W. Dong; Rowan T. Sutton (Climate Dynamics, 2013)

Characterization of MHC class II B polymorphism in bottlenecked New Zealand saddlebacks reveals low levels of genetic diversity - Jolene T. Sutton; Bruce C. Robertson; Catherine E. Grueber; Jo-Ann L. Stanton; Ian G. Jamieson (Immunogenetics, 2013)

Constraints on the partitioning of Kīlauea’s lavas between surface and tube flows, estimated from infrared satellite data, sulfur dioxide emission rates, and field observations - W. C. Koeppen; M. Patrick; T. Orr; A. J. Sutton; D. Dow; R. Wright (Bulletin of Volcanology, 2013)

A verification framework for interannual-to-decadal predictions experiments - L. Goddard; A. Kumar; A. Solomon; D. Smith; G. Boer; P. Gonzalez; V. Kharin; W. Merryfield; C. Deser; S. J. Mason; B. P. Kirtman; R. Msadek; et al. (Climate Dynamics, 2013)

The impact of resolution on the adjustment and decadal variability of the Atlantic meridional overturning circulation in a coupled climate model - Daniel L. R. Hodson; Rowan T. Sutton (Climate Dynamics, 2012)

Infection by Pythium aphanidermatum increases production of phenolics in hydroponically grown peppers and predisposes healthy plants to root rot - T. Nathaniel Owen-Going; Clifford W. Beninger; J. Christopher Hall; John C. Sutton (European Journal of Plant Pathology, 2012)

Changes of interannual NAO variability in response to greenhouse gases forcing - Buwen Dong; Rowan T. Sutton; Tim Woollings (Climate Dynamics, 2011)

Case studies in interannual to decadal climate predictability - Leon Hermanson; Rowan T. Sutton (Climate Dynamics, 2010)

Characterizing relationships between population density and nighttime imagery for Denver, Colorado: issues of scale and representation - Sharolyn J. Anderson; Benjamin T. Tuttle; Rebecca L. Powell; Paul C. Sutton (International Journal of Remote Sensing, 2010)

Does brachial artery flow-mediated dilation scale to anthropometric characteristics? - N. D. Hopkins; D. J. Green; T. M. Tinken; L. Sutton; N. McWhannell; N. T. Cable; G. Stratton; K. George (European Journal of Applied Physiology, 2010)

Climate impacts of recent multidecadal changes in Atlantic Ocean Sea Surface Temperature: a multimodel comparison - Daniel L. R. Hodson; Rowan T. Sutton; Christophe Cassou; Noel Keenlyside; Yuko Okumura; Tianjun Zhou (Climate Dynamics, 2010)

A review of climate risk information for adaptation and development planning - R. L. Wilby; J. Troni; Y. Biot; L. Tedd; B. C. Hewitson; D. M. Smith; R. T. Sutton (International Journal of Climatology, 2009)
Although the use of climate scenarios for impact assessment has grown steadily since the 1990s, uptake of such information for adaptation is lagging by nearly a decade in terms of scientific output. Nonetheless, integration of climate risk information in development planning is now a priority for donor agencies because of the need to prepare for climate change impacts across different sectors and countries. This urgency stems from concerns that progress made against Millennium Development Goals (MDGs) could be threatened by anthropogenic climate change beyond 2015. Up to this time the human signal, though detectable and growing, will be a relatively small component of climate variability and change. This implies the need for a twin‐track approach: on the one hand, vulnerability assessments of social and economic strategies for coping with present climate extremes and variability, and, on the other hand, development of climate forecast tools and scenarios to evaluate sector‐specific, incremental changes in risk over the next few decades. This review starts by describing the climate outlook for the next couple of decades and the implications for adaptation assessments. We then review ways in which climate risk information is already being used in adaptation assessments and evaluate the strengths and weaknesses of three groups of techniques. Next we identify knowledge gaps and opportunities for improving the production and uptake of climate risk information for the 2020s. We assert that climate change scenarios can meet some, but not all, of the needs of adaptation planning. Even then, the choice of scenario technique must be matched to the intended application, taking into account local constraints of time, resources, human capacity and supporting infrastructure. We also show that much greater attention should be given to improving and critiquing models used for climate impact assessment, as standard practice. Finally, we highlight the over‐arching need for the scientific community to provide more information and guidance on adapting to the risks of climate variability and change over nearer time horizons (i.e. the 2020s). Although the focus of the review is on information provision and uptake in developing regions, it is clear that many developed countries are facing the same challenges. Copyright © 2009 Royal Meteorological Society

Blue sucker stock characteristics in the Wabash River, Indiana–Illinois, USA - T. D. BACULA; D. J. DAUGHERTY; T. M. SUTTON; A. J. KENNEDY (Fisheries Management and Ecology, 2009)
Blue sucker, Cycleptus elongatus (Lesueur), populations have declined because of habitat degradation and overharvest, and little information exists on the population characteristics and stock dynamics of this species. We examined size and age structure, mortality, growth and condition of blue sucker in the Wabash River, Indiana–Illinois, USA. A total of 356 fish collected by electric fishing from June 2003 to April 2006 ranged from 238 to 775 mm total length and 85 to 5288 g wet weight. Age ranged from 3 to 16 years and annual mortality ranged from 22 to 25%. Annual growth was greatest among younger age classes (range 48–141 mm yr −1 ) and declined after age 6, likely at the onset of reproductive maturity. Variation in the relative condition factor (range 66–141) was heteroscedastic over the size range of fish sampled, perhaps attributable to seasonal differences in reproductive condition among mature fish.

Exploring multi-model atmospheric GCM ensembles with ANOVA - D. L. R. Hodson; R. T. Sutton (Climate Dynamics, 2008)

Quasi-periodic fluctuations in the Greenland–Iceland–Norwegian Seas region in a coupled climate model - Sonia R. Gamiz-Fortis; Rowan T. Sutton (Ocean Dynamics, 2007)

The Nightsat mission concept - C. D. Elvidge; P. Cinzano; D. R. Pettit; J. Arvesen; P. Sutton; C. Small; R. Nemani; T. Longcore; C. Rich; J. Safran; J. Weeks; S. Ebener (International Journal of Remote Sensing, 2007)

On the climate response of the low-latitude Pacific Ocean to changes in the global freshwater cycle - P. D. Williams; E. Guilyardi; R. T. Sutton; J. M. Gregory; G. Madec (Climate Dynamics, 2006)

Puhimau Thermal Area: A Window into the Upper East Rift Zone of Volcano, Hawaii? - K. A. McGee; A. J. Sutton; T. Elias; M. P. Doukas; T. M. Gerlach (Pure and Applied Geophysics, 2006)

Distribution and abundance of micronekton and macrozooplankton in the NW Weddell Sea: relation to a spring ice-edge bloom - Joseph Donnelly; Tracey T. Sutton; Joseph J. Torres (Polar Biology, 2006)

Temporal changes in the relationship between condition indices and proximate composition of juvenile Coregonus artedi - K. L. Pangle; T. M. Sutton (Journal of Fish Biology, 2005)
The Fulton‐condition factor ( K ) and per cent whole‐body water content were examined to determine whether these indices can estimate the proximate composition of juvenile lake herring Coregonus artedi exposed to a simulated Lake Superior winter over a 225 day laboratory experiment. The K was positively correlated to whole‐body crude lipid, crude protein, and gross energy content and negatively correlated to whole‐body water content for each sampling period of the experiment (days 75, 150 and 225). In contrast, there was only a weak positive correlation between K and whole‐body ash content. While per cent water content was negatively correlated with crude lipid, crude protein and gross energy content for each of the three sampling periods, the correlation between this predictor and ash content was only weakly negative. The indices can be used to accurately estimate temporal changes in proximate composition of juvenile lake herring during winter periods.

Fishes of the eastern Ross Sea, Antarctica - Joseph Donnelly; Joseph J. Torres; Tracey T. Sutton; Christina Simoniello (Polar Biology, 2004)

Determination of factors influencing stomach content retention by striped bass captured using gillnets - T. M. Sutton; M. J. Cyterski; J. J. Ney; M. C. Duval (Journal of Fish Biology, 2004)
The influence of mode of capture, season of capture and total body length ( L T ) on the probability of regurgitation for striped bass Morone saxatilis captured using gillnets in Smith Mountain Lake, Virginia, was examined. Overall, the mean rate of regurgitation for striped bass which contained food contents in their stomach was 8·3%. Striped bass captured by wedging had a higher mean regurgitation rate (17%) than individuals that were either entangled (5%) or gilled (2%). Striped bass caught during the autumn had approximately the same frequency of regurgitation as individuals captured during the summer (10 v . 9%), but these regurgitation rates were higher than those observed for fish during the spring sampling periods (4%). Larger striped bass were more likely to regurgitate their stomach contents than smaller individuals, with the frequency of regurgitation increasing by 0·7% for every 50 mm increase in L T . The results of this study demonstrate the importance of identifying factors that influence regurgitation of stomach contents to minimize and account for biases associated with diet data collected from striped bass captured in gillnets. Using this information, sampling recommendations for food‐habit and feeding‐rate studies involving the collection of piscivorous fishes using gillnets are made.

Absolute geostrophic currents in the East Auckland Current region - P. J. H. Sutton; T. K. Chereskin (New Zealand Journal of Marine and Freshwater Research, 2002)
Absolute geostrophic currents are estimated for the full depth of the water column off the north‐east coast of New Zealand for February 1998. This is achieved by objectively‐mapping subsurface Acoustic Doppler Current Profiler (ADCP) data using horizontal length scales determined from repeat high‐resolution Expendable Bathythermograph (XBT) data and enforcing horizontal non‐divergence. The resulting 2‐dimensional map of velocity at a single depth is used as a level of known motion. Velocities at all other depths are calculated by combining this known motion with the geostrophic shear calculated from hydrographic measurements. The flow field exhibits the expected large‐scale features: the East Auckland Current (EAUC) and the North Cape Eddy. It also indicates that these flows were underestimated by the standard use of a 2000 m level of no motion, i.e., these features penetrate 2000 m. Flows at 2000 m are found to be as large as 30–40 cm/s with a mean of 17 cm/s. This is less than the maximum flows measured by deep current meters, but significantly higher than the mean. Comparisons of the ADCP‐referenced surface flow field with the surface flow field calculated by combining climatology and TOPEX/Poseidon sea‐surface height (SSH) show general qualitative agreement. The two independent flow estimates are similar in the core of the EAUC, with the differences being c. 10 cm/s, whereas the agreement further offshore is not as good.

The seasonal cycle of tropical Pacific sea surface temperature in a coupled GCM - J. Thuburn; R. T. Sutton (Climate Dynamics, 2000)

Abstracts of presentations on selected topics at the xlvth international plant protection congress (IPPC) July 25–30, 1999 - G. Theodoridis; D. Shaner; J. Townson; J. Kemp; P. Cory; D. Bartlett; P. Sutton; D. Collins; R. Wiehert; S. O. Duke; F. E. Dayan; J. G. Romagni; et al. (Phytoparasitica, 2000)

Variable group size can further reduce animal usage in acute toxicity tests - T. J. Sutton; L. M. Reilly (Archives of Toxicology, 1991)

Contrasting modes of photosynthetic enzyme regulation in oxygenic and anoxygenic prokaryotes - N. A. Crawford; C. W. Sutton; B. C. Yee; T. C. Johnson; D. C. Carlson; B. B. Buchanan (Archives of Microbiology, 1984)